2008
DOI: 10.3233/jad-2008-15202
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy Targeting Pathological Tau Protein in Alzheimer's Disease and Related Tauopathies

Abstract: Immunotherapies that target the amyloid-β (Aβ) peptide in Alzheimer's disease (AD) have shown promise in animal and human studies. Although the first clinical trial was halted because of adverse reactions, this approach has been refined and additional trials are underway. Another important target in AD is the neurofibrillary tangles, composed primarily of hyperphosphorylated tau proteins, which correlate well with the degree of dementia. As Aβ and tau pathologies are likely synergistic, targeting both should b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
83
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(86 citation statements)
references
References 139 publications
(183 reference statements)
3
83
0
Order By: Relevance
“…Moreover, using immuno electron microscopy techniques, Meeker et al (1987) showed that antibodies could be detected within lysosomes. Thus, we propose that the antibody-mediated removal of tau aggregates is facilitated by clearance through the endosomal-lysosomal pathway (Sigurdsson, 2008(Sigurdsson, , 2009.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, using immuno electron microscopy techniques, Meeker et al (1987) showed that antibodies could be detected within lysosomes. Thus, we propose that the antibody-mediated removal of tau aggregates is facilitated by clearance through the endosomal-lysosomal pathway (Sigurdsson, 2008(Sigurdsson, , 2009.…”
Section: Introductionmentioning
confidence: 99%
“…It binds to tubulin and acts as a stabilising agent during polymerisation into microtubules in neurones. However, as a result of post-translational modifications, including hyperphosphorylation, glycosylation, ubiquitination, glycation, polyamination, nitrosylation, and truncation, the tau protein can undergo a transformation from an unfolded into a higher order structure prone to aggregation and subsequent fibrilisation [70][71][72][73]. Normal tau contains 2-3 mol phosphate/mol of the protein [70].…”
Section: Targeting Taumentioning
confidence: 99%
“…Thus design of antibodies targeting specific motifs associated with the toxic species is paramount in order to avoid disastrous consequences, such as destabilization of the microtubes and subsequent interference with axonal transport and cytoskeletal integrity [27][28][71][72][73]. One of the approaches is to design an antibody to target the phosphorylation sites that are characteristic for toxic species.…”
Section: Targeting Taumentioning
confidence: 99%
See 1 more Smart Citation
“…Sigurdsson and his colleagues suggested that anti-phospho tau antibodies could inhibit brain aggregated tau and suppress progression of tangle-related behavioural phenotype in mouse models [96].…”
Section: Anti-phospho Tau Antibodiesmentioning
confidence: 99%